Statistical analysis of the compression strength and porosity of concrete made with cement Portland type 1 and additions CPCA1 and CPCA2 (Gaceta Técnica, 2023)
In the present research, a comparison is made of the compressive strength and porosity of concrete made with Portland cement type 1, and concrete made with added cement of type CPCA1 and CPCA2, with water/cement ratios of 0,45 and 0,60.The samples come from special degree works presented at the School of Civil Engineering of the Universidad Centroccidental Lisandro Alvarado. A random sampling design with zero block factors was used, through analysis of variance where the hypothesis of equality of means is tested to compare treatments with a 99% confidence level. The rejection of the null hypothesis of equality of means was obtained in the comparison of resistance and porosity with w/c = 0.45, while for porosity with w/c = 0,60. The null hypothesis of equality of means was accepted through the Statgraphics Centurion V19 statistical software. In addition to the statistical analysis, it was obtained that the concretes made with CPCA1 and CPCA2 additives do not meet the design requirements; likewise, it was determined that the porosity of these concretes are highly porous and therefore of inadequate durability
Keywords: Portland cement type 1; added CPCA1; added CPCA2